The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1967
DOI: 10.1071/ar9670667
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology and toxicology of carbon tetrachloride in the sheep. IV. Reduction and augmentation of toxicity by selenium

Abstract: Susceptibility of sheep to toxic effects of carbon tetrachloride (CCl4) was assessed by determining the increase in plasma levels of isocitric dehydrogenase (ICD) and glutamic transaminase (GOT) and by other criteria. Susceptibility was increased by oral administration of 1 mg of selenium (Se) as sodium selenite plus 100 i.u. of tocopherol acetate on alternate days for 120 days, 2 mg Se per day for 21 days, and 6 mg Se per day for 6 days, before dosing with CCl4. Susceptibility was reduced by smaller total amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1970
1970
1970
1970

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Kanics & Rubinstein (1968) showed that carbon tetrachloride poisoned animals were unable to resynthetize liver glycogen and it seems possible that animals surviving acute experiments have a decreased liver glycogen content for a long time. Kondos & McClymont (1967) used sodium selenite and tocopherol acetate to prevent carbon tetrachloride toxicity in sheep. The resuMs were principally the same as in the P'resent study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kanics & Rubinstein (1968) showed that carbon tetrachloride poisoned animals were unable to resynthetize liver glycogen and it seems possible that animals surviving acute experiments have a decreased liver glycogen content for a long time. Kondos & McClymont (1967) used sodium selenite and tocopherol acetate to prevent carbon tetrachloride toxicity in sheep. The resuMs were principally the same as in the P'resent study.…”
Section: Discussionmentioning
confidence: 99%
“…Later it was shown that nicotinic acid also reduced the histopathological liver changes in carbon tetrachloride poisoned sheep (Gallagher 1960). Other agents effective in preventing the toxic effects of carbon tetrachloride are antioxidants (Gallagher 1961, 1962, Kondos & McClymont 1967. Gallagher (1962) found that in animals treated with antioxidants the pyridine nucleotides in the liver were maintained at normal levels despite carbon tetrachloride administration.…”
mentioning
confidence: 99%